Climatological survey and model study: Oakland-Alameda County Coliseum. Pt. 2, Wind-tunnel studies - Cermak, J. E. (Jack E.), author; Plate, Erich J., author; Fluid Mechanics Program, Fluid Dynamics and Diffusion Laboratory, College of Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1964)
Wind patterns over a 1: 384 scale model of the Oakland-Alameda County Coliseum were obtained by wind-tunnel study of the proposed complex. Motion pictures of direction indicating flags and measurements of wind speed were made for three wind directions (WNW, W and WSW), for three tree plans and for two different upper-stand arrangements at a wind speed of 30 fps. Pressure distributions around the outer wall of the circular arena structure were measured for wind speeds of 3 and 55 fps. Wind conditions over the playing field of the stadium are generally such that wind speeds are less than 60 percent of ambient air speed. Relatively high wind speeds were directed along the windward side of the arena, across the bridge connecting arena and stadium, and over the berm from left- field to right of center field.
Wind-tunnel model study
CER64JEC-EJP22.
June 1964.
For Skidmore, Owings and Merrill.
Keywords: Stadiums -- California -- Oakland -- Aerodynamics; Wind tunnel models; Buildings -- Aerodynamics